Econometric analysis of the determinants of air cargo services supply in Latin America and the Caribbean. (May 2023) - Fageda, Xavier; Fioravanti, Reinaldo; Ricover, Andy; Café, Eduardo; Ansaldo, Mariano
Abstract: This paper examines econometrically the determinants of air cargo supply in the countries of Latin American and the Caribbean (LAC) using city-pair data for 2011–2020. We find that air cargo supply tends to be concentrated in airports located in highly populated cities. The relationship between income and air cargo supply is more complex although its positive effect seems to be more consistent for dedicated cargo flights. In addition, we only find a negative relationship between distance and air cargo supply when we focus on belly cargo. Low-cost airlines spur cargo in passenger flights buy they do not have any positive role in dedicated cargo flights. Free trade agreements seem to contribute positively to a greater supply of air cargo, but this effect is concentrated on belly cargo and intra-regional routes. In contrast, the quality of the infrastructure at the airport of origin positively impacts air cargo supply only on dedicated flights and extra-regional routes. Finally, we do find evidence that a more intense competition between airlines and the greater use of wide-body aircraft have a positive effect on cargo supply. Highlights: We examine air cargo services supply at origin/destination level. We find a weak influence of distance on dedicated cargo flights. Low-cost airlines spur cargo in passenger flights but not in dedicated cargo flights. Free trade agreements impact positively on belly cargo and intra-regional routes. Infrastructure quality has positive effects on cargo flights and extra-regional routes.